Peningkatan Pengetahuan Masyarakat Desa Kuala Tolam tentang Mitigasi Bencana Ekosistem Gambut Partisipatif - Gandhiko Mohta; Maryani Maryani; Erwanda Trio Bintan Sabri; Anesha Allasselcida; Dinda Tri Agustina; Lefdi Agung Nugraha; Agung Kartika Putra; Hanifah Ikhsani; Evi Sribudiani; Nurul Qomar; Muhammad Mardhiansyah (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aimed to improve the knowledge of residents of Kuala Tolam Village regarding drought control, flood management, peatland ecosystems, and riverbank landslide mitigation in areas vulnerable to hydrometeorological hazards. The education program was conducted through material delivery, discussions, and pre-test and post-test evaluations using a questionnaire. Data were analyzed using IBM SPSS Statistics 20 to describe respondent characteristics and to examine knowledge improvement using a paired sample t-test. The results showed that 66.67% of participants were initially in the low knowledge category; however, after the intervention, all participants improved to the moderate and high categories. The mean knowledge score increased from 47.33 to 69.73, with a statistically significant difference (p 0.05). This improvement was supported by the relevance of the materials, including peatland hydrology, drought control, flood mitigation, and riverbank bioengineering. Participatory education is therefore important for strengthening community capacity and village preparedness in managing environmental risks in peatland ecosystems.